ALDH Expression in Angiosarcoma of the Lung: A Potential Marker of Aggressiveness? - Aramini, Beatrice; Masciale, Valentina; Bianchi, Daniel; Manfredini, Beatrice; Banchelli, Federico; D'Amico, Roberto; Bertolini, Federica; Dominici, Massimo; Morandi, Uliano; Maiorana, Antonino (Frontiers in Medicine, 2020)
Background: Primary angiosarcoma of the lung is a very aggressive rare malignant disease resulting in a severe prognosis (1). This type of cancer represents about 2% of all soft tissue sarcomas and has a high rate of metastasis through the hematogenous route. For the rarity of this malignant vascular tumor it is still challenging to set a diagnosis (1). The diagnostic features that have thus far been considered include primarily clinical and radiological findings. In some cases, immunohistochemical characteristics based on the most common markers used in pathology have been described. The aim of this report is to present two cases of angiosarcoma of the lung in which the aldehyde dehydrogenase (ALDH) marker was analyzed by immunohistochemistry. Methods: We report two cases of angiosarcoma of the lung in patients underwent lung surgery at our Unit. In addition to the standard histopathological analysis for this disease, immunohistochemistry using an ALDH1A1 antibody was performed in both of the cases. For ALDH quantification, a semi-quantitative method based on the positivity of the tumor cells was used: 0 (<5%), 1 (5–25%), 2 (>25–50%), 3 (>50–75%), 4 (>75%). Results: One patient with recurrent lung disease survived, achieving complete remission after chemo- and radiotherapy. The second patient died of recurrent disease within 5 years of diagnosis. ALDH1A1 was evaluated in both of these cases using an immunohistochemistry scoring system based on the positivity for this marker. The scores were consistent with the patients' clinical outcomes, as the lower (score 1) was observed in the patient with the better clinical outcome, while the higher (score 3) was seen in the patient with the worse outcome. Conclusion: Our data suggest that ALDH may be an important clinical marker in angiosarcoma of the lung. Although further studies need to be performed in a larger cohort of patients, we believe that, if the results will be confirmed, ALDH1A1 may be used to stratify patients in terms of prognosis and for targeted therapy.